Protection Intellectual Property Right in Indonesia and Holland (Study Comparative Both Country) - Hafid Zakariya; Dardiri Hashim; Nurul Hidayah (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
This article has aim for knowing how protection Intelectual property right in Indonesia and Holland and how effort for protect IPR particularly in copyright. Methodologies research in study normative approach, where date use is regulation both country, and see many literature, we use internet for looking for date. Result this article there is difference for protection in Indonesia and Holand, in Indonesia government not optimal for reduce unfair ipr, in Holland optimal use rule for law enforcement. Keywords: Protection, IP